PELATIHAN PEMILAHAN SAMPAH UNTUK DUSUN SUMBERINGIN DESA WRINGINSONGO KABUPATEN MALANG - Beauty Anggraheny Ikawanty; Mila Fauziyah; Mohammad Luqman; Muhammad Khairuddin; Ari Murtono (Jurnal Pengabdian kepada Masyarakat, 2024)
Sumberingin Hamlet is one of two hamlets located in Wringinsongo village, Tumpang sub-district, Malang Regency. The people work in the agricultural, livestock and industrial sectors. So with thousands of people in one village and the majority of livelihoods in the village itself, the amount of rubbish thrown away every day is increasing. Household waste produced by each family is cleaned/picked up by officers per RT and sent to the final disposal site (TPA) available in the village. Every day, if the average weight of waste produced by each family is 5 kg, then every day the village will produce around 4500 kg of waste. The landfill in Sumberingin hamlet is located very far away and means of transportation to the landfill are very limited. So that rubbish piles up in landfills and is not managed, causing odors and pollution to the surrounding environment. Waste disposal in Sumberingin hamlet is still divided between organic and inorganic waste. This can be seen from the fact that there is only one trash bin in each household. Therefore, this community service focuses on partner groups of Sumberingin hamlet women for waste sorting training. Waste sorting is the activity of grouping and separating waste according to the type, quantity and/or nature of the waste. Waste sorting at home can be grouped into 3, namely organic waste, inorganic waste and residual waste.